Draft Annual Plan 1968-69 Union Territory of Delhi Planning Department Delhi Administration - Planning Commission (Planning Commission, 1968)
An outlay of Rs23 lakhs has been provided in the fourth Plan for various schemes under this head. In 6179-66, the expenditure was of the order of Rs 2.5 lakhs against the approved outlay of Rs 4 lakhs. The shortfall was partly due to the fact that the outlay earmarked for Relief and Guarantee fund could not be utilised as the question of creation of this fund in the Union Territories is still under the consideration of the Government of India and partly because certain posts under the plan schemes remained vacant.
Union Territory of Delhi Planning Department Delhi Administration